Activity of New Method Schools in Turkey (End of Xix Century, Beginning of Xx Century) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
At the end of the 19th century and the beginning of the 20th century, a movement covering large political, social, economic and cultural spheres was formed in the region of Turkestan. . Today, we consider this act as a revolutionary act. They realized that the main goal of the Jadids was to achieve freedom only by opening schools of their new method - "Usuli Jadid" and enlightening the people. This article examines the opening of the first "new method" schools founded by the Jadids and their conditions, as well as the internal and external factors that gave rise to this movement.